2021
DOI: 10.3389/fcell.2021.703218
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Short-Chain Fatty Acids and Bile Acids in Intestinal and Liver Function, Inflammation, and Carcinogenesis

Abstract: During the past decade, researchers have investigated the role of microbiota in health and disease. Recent findings support the hypothesis that commensal bacteria and in particular microbiota-derived metabolites have an impact on development of inflammation and carcinogenesis. Major classes of microbial-derived molecules such as short-chain fatty acids (SCFA) and secondary bile acids (BAs) were shown to have immunomodulatory potential in various autoimmune, inflammatory as well as cancerous disease models and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 137 publications
0
41
0
Order By: Relevance
“…In addition, the extremely small size of the SCFAs allows them to enter the nucleus directly and act as inhibitors of histone deacetylase (HDAC) [ 55 ]. Histone acetylation is a process that can promote the loosening of the chromatin structure of target genes to enhance gene transcription, but HDAC inhibits this process [ 56 ].…”
Section: Anti-inflammatory Mechanism Of Scfasmentioning
confidence: 99%
“…In addition, the extremely small size of the SCFAs allows them to enter the nucleus directly and act as inhibitors of histone deacetylase (HDAC) [ 55 ]. Histone acetylation is a process that can promote the loosening of the chromatin structure of target genes to enhance gene transcription, but HDAC inhibits this process [ 56 ].…”
Section: Anti-inflammatory Mechanism Of Scfasmentioning
confidence: 99%
“…Hence, metabolomics study is important in categorizing breast cancer into different types and stages, as it uses accurate methods and requires less time for analysis. Metabolites from secondary bile acid metabolism, amino acid degradation, short-chain fatty acid production, and deconjugated hormones can be measured to predict tamoxifen resistance, hormone-induced apoptosis, cancer aggressiveness, and histone deacetylase (HDAC) inhibition [ 55 , 56 , 57 ].…”
Section: Metabolomics Profile Of Breast Cancersmentioning
confidence: 99%
“…Mucin, in turn, promotes host-microbe symbiosis and enhances gut barrier integrity. Taken together, RS supplementation potentially regulates the release of various metabolites by symbiotic bacteria, including bioactive peptides, BAs, and EnEth, which are beneficial to the host as vital modulators of immunometabolism ( 62 66 ). This further indicated that dietary RSs can alleviate NAFLD through the GLA.…”
Section: Potential Mechanisms Of Resistant Starches On Regulating The...mentioning
confidence: 99%